2007
DOI: 10.2486/indhealth.45.301
|View full text |Cite
|
Sign up to set email alerts
|

A Short Nap and Natural Bright Light Exposure Improve Positive Mood Status

Abstract: While the effects of a short nap on performance and arousal level have been well investigated, less attention has been paid to its effects on mood status. The aim of the present study was to examine the effects of a short nap and natural bright light exposure on mood status. Participants were 16 healthy females who were on average 38.1 (SD = 2.68) yr old. From 11:00 to 12:00, the participants carried out a set of tasks twice with baseline lighting (<100 lux). From 12:40 to 13:10, they were subjected to three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 46 publications
(67 reference statements)
1
37
0
Order By: Relevance
“…Laboratory-based studies detailed the beneficial effects of napping on several systems (cognitive, stress, immune or pain functions). Furthermore, pilot nap-based laboratory studies have reported that a midday nap of 20-30 min improved mood status and mental states, 197,198 suggesting that a proper application of a short nap could positively affect the aforementioned functions.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory-based studies detailed the beneficial effects of napping on several systems (cognitive, stress, immune or pain functions). Furthermore, pilot nap-based laboratory studies have reported that a midday nap of 20-30 min improved mood status and mental states, 197,198 suggesting that a proper application of a short nap could positively affect the aforementioned functions.…”
Section: Discussionmentioning
confidence: 99%
“…[77] A final concern is that several potential moderators could not be considered, including biological sex, [78] variations in exposure to bright light resulting from indoor versus outdoor exercise, [79] and variations in sleepiness resulting from the prior night's sleep or daytime naps. [80] Understanding the effect of acute exercise on energy and fatigue is also limited in part because of inadequate reporting of physical activity history as well as the dimensions of the acute exercise stimulus (intensity, duration, mode). Without these data, it is difficult to determine what aspect of the exercise is responsible for changes in energy or fatigue.…”
Section: Fatigue Moderatorsmentioning
confidence: 99%
“…The combination of bright light exposure and caffeine intake may scale down melatonin secretion (hormone associated with sleep) and increase alertness, body temperature, and performance after having sleep deprivation in the previous night (Wright et al 2000). There are even suggestions that short duration of bright light exposure after midday napping can help prevent sleep inertia (Phipps-Nelson et al 2003), improve mood stability, alertness, and performance (Kaida et al 2007), and even beneficial for social interaction and job satisfaction at the workplace (Judge and Ilies 2004). However, there is no consensus on bright light effects since there is also a report that emotional stability and sleepiness are worsened with only the exposure to bright light (Burgess et al 2002).…”
Section: Neuroscience Perspective Of Midday Nappingmentioning
confidence: 97%